Homogeneous Anodic TiO2 Nanotube Layers on Ti–6Al–4V Alloy with Improved Adhesion Strength and Corrosion Resistance. Issue 12 (15th April 2019) - Hu, Nan; Hu, Tao; Gao, Ang; Gao, Nong; Starink, Marco J.; Chen, Ying; Sun, Wanting; Liao, Qing; Tong, Liping; Xu, Xiaochang; Chu, Paul K.; Wang, Huaiyu
Abstract: Hexagonal TiO2 nanotubes (TNTs) arrays are generally fabricated on Ti‐based substrates for some biomedical purposes, but the TNT layers constructed on conventionally processed Ti alloys are usually inhomogeneous because the substrates typically contain both the α and β phases. In this work, high‐pressure torsion (HPT) is applied to obtain a saturated single α‐phase microstructure in Ti–6Al–4V alloys via strain‐induced β phase dissolution. Homogeneous anodic TNT layers with three different morphologies, one‐step nanoporous, one‐step nanotubular, and two‐step nanoporous structures, are electrochemically fabricated on the ultrafine‐grained (UFG) Ti–6Al–4V alloy substrates after HPT processing, whereas the TNT layers prepared on coarse‐grained substrates are normally inhomogeneous. More notably, the TNT layers show significantly improved adhesion strength to the UFG substrate as well as better corrosion resistance compared to those on the conventionally processed Ti–6Al–4V substrates. X‐ray diffraction analysis, scanning electron microscopy in combination with electron backscatter diffraction, and transmission electron microscopy indicate that the improvement is due to a larger dislocation density in the UFG substrate as well as strain‐induced β phase dissolution. Abstract : Homogeneous monophasic TiO2 nanotubes (TNTs) arrays have been anodically fabricated on dual‐phasic (α + β) Ti–6Al–4V alloys processed by high pressure torsion. The homogeneous TNTs demonstrate improved corrosion resistance and better adhesion strength to the substrate compared to their counterparts on a conventional Ti–6Al–4V substrate. The image expresses morphologies of both TNT layers and results of their nanoscratching tests.